Participação do fator de liberação de corticotrofina (CRF) no Locus coeruleus na resposta respiratória à hipercapnia - Miranda, Jolene Matos Incheglu de (Universidade Federal de São Carlos, 2015)
Locus coeruleus (LC) is a pontine noradrenergic group that acts as a central chemoreceptor to CO2/pH and it is involved in the cognitive aspects of stress response and it is associated with a large number of physiological and behavioral processes, including sleepwake cycle, feeding, cardiovascular and respiratory control, nociception, thermoregulation and learning. The LC has also been implicated in the cognitive aspects of stress responses, in part through the action of corticotropin releasing factor (CRF), which when released in these situations increases the firing frequency of LC noradrenergic neurons. CRF is the largest stimulator of the pituitary secretion of ACTH (adrenocorticotropic hormone) and their receptors (types 1 and 2) are widely distributed in the central nervous system, including the LC. Thus, we tested the involvement of CRF1 receptors (CRF1) located in the LC in the ventilatory and thermal responses induced by hypercapnia (7%CO2) in rats. To this end, we injected antalarmin (a CRF1 antagonist, 0.05 and 0,1 μg/0.1 μL) into the LC of male Wistar rats. Pulmonary ventilation (VE) and body temperature (Tb, dataloggers) were measured in air and followed by 7% CO2 in unanesthetized rats. There were no differences in body temperature between groups under normocapnia and hypercapnia. We observed an increased ventilation in normocapnia, at 5 to 15 minutes after microinjection of antalarmin (dose 0.1 μg / 0.1 μL) compared to the control, due to an increase in tidal volume. The hypercapnic response in antalarmine treated animals was higher compared to control groups. The dose of 0.05 μg / 0.1 μL caused an increase in ventilation 15 min after CO2 exposure and this response increased further with the dose of 0.1 μg / 0.1 μL at 30 minutes after hypercapnia, due to an increased tidal volume. Our results suggest that CRF1 receptors in the LC exert a tonic inhibitory role in the ventilation and the inhibitory modulation of the respiratory response to CO2.
Keywords: Locus coeruleus; Fator de liberação de corticotrofina; Hipercapnia; Ventilação; Quimiorrecepção; CRF; CRF1 receptors; Hypercapnia; Ventilation; Chemoreception; CIENCIAS BIOLOGICAS::FISIOLOGIA